Microeconomic Evidence of Creative Destruction in Industrial and Developing Countries - Bartelsman, Eric (Washington, DC: World Bank, 2012)
This paper analyzes the process of creative destruction across 24 countries and 2-digit industries. This approach harmonizes firm level data across countries, enabling international comparisons and the identification of country-specific as opposed to sectoral and time effects factors. All countries display a massive reallocation of resources, with the entry and exit of many firms in all markets, the failure of many newcomers and the expansion of successful ones. This process of creative destruction affects productivity directly, by reallocating resources towards more productive uses, but also indirectly through the effects of increased market contestability. While entry and exit rates are fairly similar across industrial countries, post entry performance differs markedly between Europe and the U.S., a potential indication of the importance of barriers to firm growth as opposed to barriers to entry. Transition economies show an even more impressive process of creative destruction and those that have made the most progress toward a market economy show better outcomes.